Characterization Studies on Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) Complexes with New Ligands Derived from Anthraquinone Substance - Aziz, Kawakib A.; Yousif, Thana Y. (Iraqi Journal of Science, 2022)
This work involves preparation of new metal complexes via reaction of two anthraquinone ligands with Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) metal ions . The ligands are prepared by treatment of 1- and 2-anthraquinone with acetic anhydride.      The complexes are characterized by different physicochemical methods; microelemental analysis, molar conductivity, FT-IR, UV-Vis spectra and magnetic measurements. The discussion of the outcome data of the prepared complexes indicates that all complexes are octahedral.      The biological activity properties of the ligands and most of their complexes are studied using gram-positive and gram-negative bacteria, which indicate that only two of the complexes show biological activity.